Preschool Teacher Education Program to Bring Pre Service Preschool Teachers in Professional Ethics Values - Alan, Ümran; Özden, Muhammet; YAĞAN, SEVCAN (My University, 2011)
As an application area of ethics, professional ethics can be define as the accepted rules, approaches, attitudes and behavior that one must consider and individualize while professing a job and share with others in same profession. All profession groups have their own ethical principles. Parallel to this as an profession Pre-school Teaching has its own ethical principles. However when Program in Pre-school Education is analyzed it is seen that there is not any course that primarily aims to get students comprehend professional ethic principles. Especially, the internalization and application of professional ethic by the pre-school teachers working with young children will contribute the comprehension of ethic rules by next generations. In this context, it is important for pre-school teachers to know and internalize professional ethic principles. The basic aim of this survey model employed study determine the ideas and opinions of 4th grade Pre-school Education Program students and the factors and courses that served to form those ideas and opinions. Towards this basic aim focus group interview was done with 10 4th grade preschool education program students. The purposes of choosing focus group interview for data gathering is provide students exchange their consideration with their friends and researchers and examine the subject detailed. Data will be analyzed by descriptive analysis technique and results will be presented and discussed in the congress.
Keywords: Pre School Teaching Professional Ethics; Pre Service Pre School Teachers